EFEKTIVITAS PEMUNGUTAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN DI KECAMATAN KARANG BAHAGIA KABUPATEN BEKASI TAHUN 2018-2023 - Dahuri, Adin; Yani, Yani; Syadat, Fahrul Anwar (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The research describes the effectiveness collection of Land and Building Tax of Rural and Urban (PBB P2) of Karang Bahagia District in Rekasi Regency within the periode of 2015'2023. Data of PBB-P2-collections showed an average achievement of 48,31% per year or ranged from 36,56% to 56,44%. The average achievement of PBB-P2 collection as well as achievemrs per year within the periode of 2018-2023 concluded that the efforts of collection were ineffective due to revenues realuxation could not reach predetermined target. The ineffectiveness of PBB-P2 collection is due to some obstacles such as. : targets determination were muah higher so that difficult to.be achieved, the obedience of some tax payers that should be encourage, the ineffective use of